2014
DOI: 10.7475/kjan.2014.26.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to Quality of Life of Patients with Ulcerative Colitis

Abstract: Purpose:The purpose of this study was to identify factors related to the quality of life of patients with ulcerative colitis. Methods: A total 116 patients with ulcerative colitis were asked on general characteristics, illness-related characteristics, depression, and quality of life. The collected data were analyzed by t-test, ANOVA, and stepwise multiple regression. Results: As for depression the 81.03% were normal, the 8.62% were mild depression, the 6.90% were moderated depression, and the 3.45% were severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Self‐rated health reflects individuals' disease status and, among older adults, functional status (Meng et al, 2014); it is also associated with quality of life in patients with chronic diseases (Yoo et al, 2014). Previous studies have found subjective health status to predict mortality in patients with diabetes (McEwen et al, 2009) and, among patients with type 2 diabetes, to be significantly associated with self‐management (Bishwajit et al, 2017; Jung et al, 2015) and glycaemic control (Park, 2010; Won et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Self‐rated health reflects individuals' disease status and, among older adults, functional status (Meng et al, 2014); it is also associated with quality of life in patients with chronic diseases (Yoo et al, 2014). Previous studies have found subjective health status to predict mortality in patients with diabetes (McEwen et al, 2009) and, among patients with type 2 diabetes, to be significantly associated with self‐management (Bishwajit et al, 2017; Jung et al, 2015) and glycaemic control (Park, 2010; Won et al, 2014).…”
Section: Introductionmentioning
confidence: 99%